ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

An Innovative Arteriovenous (AV) Loop Breast Cancer Model Tailored for Cancer Research - An, Ran; Strissel, Pamela; Al-Abboodi, Majida; Robering, Jan Willem; Reakasame, Supachai; Eckstein, Markus; Peddi, Ajay; Hauck, Theresa; Bäuerle, Tobias; Boccaccini, Aldo R.; Youssef, Almoatazbellah; Sun, Jiaming; et al. (Bioengineering, 2022)
Animal models are important tools to investigate the pathogenesis and develop treatment strategies for breast cancer in humans. In this study, we developed a new three-dimensional in vivo arteriovenous loop model of human breast cancer with the aid of biodegradable materials, including fibrin, alginate, and polycaprolactone. We examined the in vivo effects of various matrices on the growth of breast cancer cells by imaging and immunohistochemistry evaluation. Our findings clearly demonstrate that vascularized breast cancer microtissues could be engineered and recapitulate the in vivo situation and tumor-stromal interaction within an isolated environment in an in vivo organism. Alginate–fibrin hybrid matrices were considered as a highly powerful material for breast tumor engineering based on its stability and biocompatibility. We propose that the novel tumor model may not only serve as an invaluable platform for analyzing and understanding the molecular mechanisms and pattern of oncologic diseases, but also be tailored for individual therapy via transplantation of breast cancer patient-derived tumors.
CRIS-Team Scopus Importer:2022-07-15
Keywords: animal model; arteriovenous loop; breast cancer

Human adipose-derived stem cells support lymphangiogenesis in vitro by secretion of lymphangiogenic factors - Ahmadzadeh, Nima; Robering, Jan Willem; Kengelbach-Weigand, Annika; Al-Abboodi, Majida; Beier, Justus; Horch, Raymund E.; Boos, Anja (Experimental Cell Research, 2020)
Lymphedema is a chronic progressive disease ultimately resulting in severe, disfiguring swelling and permanent changes of the affected tissues. Presently, there is no causal treatment approach of lymphedema. Therefore, most therapies are purely symptomatic. However, the recent use of stem cell-based therapies has offered new prospects for alternative treatment options. The present study was performed to investigate the effects of human adipose-derived stem cells (ADSCs) on human dermal lymphatic endothelial cells (HDLECs) in terms of basic in vitro lymphangiogenic assays (WST-8 assay, scratch assay, transmigration assay, sprouting assay, tube formation assay). The influence of ADSC-conditioned medium (ADSC-CM) on HDLECs was compared to recombinant VEGF-C, bFGF and HGF. Further ADSC-CM was characterized by protein microarray and enzyme-linked immunosorbent assay (ELISA). Although key-lymphangiogenic growth factors - like VEGF-C - could only be detected in low concentrations within the conditioned medium (CM), HDLECs were potently stimulated to proliferate, migrate and to form tube like structures by ADSC-CM. Despite concentrations more than hundredfold higher than those found in the conditioned medium, stimulation with recombinant VEGF-C, bFGF and HGF was still weaker compared to ADSC-CM. These results highlight the effectiveness of growth factors secreted by ADSC to stimulate HDLEC, potentially providing a promising new therapeutic approach for the treatment of lymphedema.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Adipose-derived stem cells (ADSCs); Cell therapy; Human dermal lymphatic endothelial cells (HDLECs); Lymphangiogenesis; Lymphedema; Secretome

Lysophosphatidic acid activates satellite glia cells and Schwann cells - Robering, Jan Willem; Gebhardt, Lisa; Wolf, Katharina; Kühn, Helen; Kremer, Andreas; Fischer, Michael Jochen Marco (Glia, 2019)
Pruritus is a common and disabling symptom in patients with hepatobiliary disorders, particularly in those with cholestatic features. Serum levels of lysophosphatidic acid (LPA) and its forming enzyme autotaxin were increased in patients suffering from hepatic pruritus, correlated with itch severity and response to treatment. Here we show that in a culture of dorsal root ganglia LPA 18:1 surprisingly activated a large fraction of satellite glia cells, and responses to LPA 18:1 correlated inversely with responses to neuronal expressed transient receptor potential channels. LPA 18:1 caused only a marginal activation of heterologously expressed TRPV1, and responses in dorsal root ganglion cultures from TRPV1-deficient mice were similar to controls. LPA 18:1 desensitized subsequent responsiveness to chloroquine and TGR5 agonist INT-777. The LPA 18:1-induced increase in cytoplasmatic calcium stems from the endoplasmatic reticulum. LPA receptor expression in dorsal root ganglia and Schwann cells, LPAR1 immunohistochemistry, and pharmacological results indicate a signaling pathway through LPA receptor 1. Peripheral rat Schwann cells, which are of glial lineage as the satellite glia cells, were also responsive to LPA 18:1. Summarizing, LPA 18:1 primarily activates rather glial cells than neurons, which may subsequently modulate neuronal responsiveness and sensory sensations such as itch and pain.
CRIS-Team WoS Importer:2019-04-04

Mesenchymal stem cells promote lymphangiogenic properties of lymphatic endothelial cells - Robering, Jan Willem; Weigand, Annika; Pfuhlmann, Romy; Horch, Raymund E.; Beier, Justus; Boos, Anja (Journal of Cellular and Molecular Medicine, 2018)
Lymphatic metastasis is one of the main prognostic factors concerning long-term survival of cancer patients. In this regard, the molecular mechanisms of lymphangiogenesis are still rarely explored. Also, the interactions between stem cells and lymphatic endothelial cells (LEC) in humans have not been well examined. Therefore, the main objective of this study was to assess the interactions between mesenchymal stem cells (MSC) and LEC using in vitro angiogenesis assays. Juvenile LEC were stimulated with VEGF-C, bFGF, MSC-conditioned medium (MSC-CM) or by co-culture with MSC. LEC proliferation was assessed using a MTT assay. Migration of the cells was determined with a wound healing assay and a transmigration assay. To measure the formation of lymphatic sprouts, LEC spheroids were embedded in collagen or fibrin gels. The LEC's capacity to form capillary-like structures was assessed by a tube formation assay on Matrigel® . The proliferation, migration and tube formation of LEC could be significantly enhanced by MSC-CM and by co-culture with MSC. The effect of stimulation with MSC-CM was stronger compared to stimulation with the growth factors VEGF-C and bFGF in proliferation and transmigration assays. Sprouting was stimulated by VEGF-C, bFGF and by MSC-CM. With this study, we demonstrate the potent stimulating effect of the MSC secretome on proliferation, migration and tube formation of LEC. This indicates an important role of MSC in lymphangiogenesis in pathological as well as physiological processes.
EVALuna2:211472

Proangiogenic effects of tumor cells on endothelial progenitor cells vary with tumor type in an in vitro and in vivo rat model. - An, Ran; Schmid, Rafael; Klausing, Anne; Robering, Jan Willem; Weber, Manuel; Bäuerle, Tobias; Detsch, Rainer; Boccaccini, Aldo R.; Horch, Raymund E.; Boos, Anja; Weigand, Annika (The FASEB Journal, 2018)
Endothelial progenitor cells (EPCs) contribute to neovascularization in tumors. However, the relationship of EPCs and tumor-induced angiogenesis still remains to be clarified. The present study aimed at investigating the influence of 4 different tumor types on angiogenic properties of EPCs in an in vitro and in vivo rat model. It could be demonstrated that in vitro proliferation, migration, and angiogenic abilities and genetic modifications of EPCs are controlled in a tumor-type-dependent manner. The proangiogenic effect of mammary carcinoma, osteosarcoma, and rhabdomyosarcoma cells was more pronounced compared to colon carcinoma cells. Coinjection of encapsulated tumor cells, especially mammary carcinoma cells, and EPCs in a rat model confirmed a contributing effect of EPCs in tumor vascularization. Cytokines secreted by tumors such as monocyte chemoattractant protein 1, macrophage inflammatory protein 2, and TNF-related apoptosis-inducing ligand play a pivotal role in the tumor cell-EPC interaction, leading to enhanced migration and angiogenesis. With the present study, we were able to decipher possible underlying mechanisms by which EPCs are stimulated by tumor cells and contribute to tumor vascularization. The present study will contribute to a better understanding of tumor-induced vascularization, thus facilitating the development of therapeutic strategies targeting tumor-EPC interactions.-An, R., Schmid, R., Klausing, A., Robering, J. W., Weber, M., Bäuerle, T., Detsch, R., Boccaccini, A. R., Horch, R. E., Boos, A. M., Weigand, A. Proangiogenic effects of tumor cells on endothelial progenitor cells vary with tumor type in an in vitro and in vivo rat model.

Specific features of ex-obese patients significantly influence the functional cell properties of adipose-derived stromal cells - Schmitz, Deborah; Robering, Jan Willem; Weisbach, Volker Günter; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja; Kengelbach-Weigand, Annika (Journal of Cellular and Molecular Medicine, 2022)
Adipose-derived stromal cells (ADSC) are increasingly used in clinical applications due to their regenerative capabilities. However, ADSC therapies show variable results. This study analysed the effects of specific factors of ex-obese patients on ADSC functions. ADSC were harvested from abdominal tissues (N = 20) after massive weight loss. Patients were grouped according to age, sex, current and maximum body mass index (BMI), BMI difference, weight loss method, smoking and infection at the surgical site. ADSC surface markers, viability, migration, transmigration, sprouting, differentiation potential, cytokine secretion, telomere length and mtDNA copy number were analysed. All ADSC expressed CD73, CD90, CD105, while functional properties differed significantly among patients. A high BMI difference due to massive weight loss was negatively correlated with ADSC proliferation, migration and transmigration, while age, sex or weight loss method had a smaller effect. ADSC from female and younger donors and individuals after weight loss by increase of exercise and diet change had a higher activity. Telomere length, mtDNA copy number, differentiation potential and the secretome did not correlate with patient factors or cell function. Therefore, we suggest that factors such as age, sex, increase of exercise and especially weight loss should be considered for patient selection and planning of regenerative therapies.
CRIS-Team Scopus Importer:2022-07-22
Keywords: adipose-derived stromal cells; bariatric surgery; body mass index; cell function; regenerative medicine

Tissue Engineering of Lymphatic Vasculature in the Arteriovenous Loop Model of the Rat - Robering, Jan Willem; Al-Abboodi, Majida; Titzmann, Adriana; Horn, Inge; Beier, Justus; Horch, Raymund E.; Kengelbach-Weigand, Annika; Boos, Anja (Tissue Engineering - Part A, 2020)
Various therapeutic approaches, for example, in case of trauma or cancer require the transplantation of autologous tissue. Depending on the size and the origin of the harvested tissue, these therapies can lead to iatrogenic complications and donor-site morbidities. In future, these side effects could be avoided by transplanting artificially generated tissue consisting of different cell types and matrix components derived from the host body. Tissue that is grown in the patient could be advantageous compared with the more simply structuredin vitro-grown alternatives. To overcome the limitations of graft vascularization, the arteriovenous (AV) loop technique has been established for different tissues in the last years and was adapted for lymphatic tissue engineering in the present study. We utilized the AV loop technique to grow human lymphatic vasculaturein vivoin the Rowett nude (RNU) rat. A combination of human lymphatic endothelial cells (LECs) and bone marrow-derived mesenchymal stem cells was implanted in a fibrin matrix surrounding the AV loop. After 2 or 4 weeks of implantation, the animals were perfused and the tissue was harvested. It could be demonstrated by immunohistochemistry for human LYVE1, human CD31, and murine podoplanin that the implanted cells formed human lymphatic vasculature in the AV loop chamber. Beside development of murine podoplanin-positive vasculature in the AV loop tissue, vasculature positive for human marker proteins developed in comparable numbers. This suggests that implanted LECs are able to improve the lymphatic vascularization of the newly engineered tissue. Thus, we were able to establish anin vivotissue engineering method to generate lymphatic vascularized soft tissue. An axially vascularized transplantable lymphatic vessel network was engineered without requiring advanced cell culture equipment, rendering the lymphatic AV loop highly suitable for applied regenerative medicine. Impact statement Various surgical procedures require the transplantation of autologous harvested tissue, for example, the vascularized lymph node transfer for the treatment of lymphedema. Tissue-engineered transplants could be used instead of autologous transplants and thereby help to reduce the side effects of those therapies. However,in vitrotissue engineering of large constructs requires a lot of know-how as well as advanced cell culture equipment, which might not be accessible in every hospital.In vivotissue engineering approaches like the presented technique for the generation of transplantable networks of lymphatic vasculature could serve as an alternative forin vitrotissue engineering approaches in clinical settings.
CRIS-Team WoS Importer:2020-10-16